Pengadilan Sebagai Lembaga Penegakan Hukum (Perspektif Civil Law dan Common Law) - Triningsih, Anna (Mahkamah Konstitusi Republik Indonesia, 2015)
Law, as an justice institution run its functions through a specific process towards a certain direction in order to achieve justice. Justice now a days is needed as something concrete as the fulfillment of the most basic needs of the community. Law enforcement, in parliamentary life is run by the Government (the executive organs) and through the courts (judicial organ).There are different approaches in law enforcement. The rule of law in the Civil Law System which is shared by the countries in the European continent or land use law, also known as legal approach. In the Common Law System which is shared by the United Kingdom and the United Kingdom speaking countries, using the administration approach of the Administration, called the administration of justice. Implementation of the fundamental principles of the law, or because of its emphasis on the steps of a procedure in the event properly can make the law as an unrealistic myth, inefficient and far from the purpose of the law and implies the occurrence of loss of trust from the community, while the basic principles of administration, because of its emphasis on the achievement of business objectives efficiently will have implications for the lack of certainty in law enforcement that is essential for the achievement of Justice for everyone. Besides that addition, it also can be an opportunity for the Court arbitrariness because discretion has its wide open room. Every Legal Approach has its own advantages and disadvantages. Making option to choose which legal approach as an appropriate and good policy in law enforcement is related to the characteristics and level of knowledge of the community also the environment where these law applied.